Kanon portretowania w historiografii bizantyńskiej na przykładzie portretu Boemunda w Aleksjadzie Anny Komneny - Kokoszko, Maciej (Acta Universitatis Lodziensis. Folia Historica, 2000)
Anna Komnena (1083-1153/1154), the daughter of emperor Alexios I, was involved in the most important political events of her father’s reign. Not only could she witness the developments of her lifetime, but she also managed to put her brand on her father’s and brother’s policy. That is why she gained excellent competence both in political and religious developments of the time. Her superb education contributed to an exceptionally high merit of the work she wrote. One of the most critical problems Alexios I had to face was the Norman expansion, which during his reign assumed a form of continual wars waged by the Empire, first against Robert Guiscard, and later his son, Boemund. The emperor did not succeed in eliminating the Norman danger because he was also forced to combat numerous incursions of the Turks. Anna Komnena included in her work a number of literary portraits. One of them describes Boemund. The description matched against the descriptions of emperors Alexios I and John I as well as Boemund’s father, Robert Guiscard, proved to imitate physiognomical rules. Since the portrait of Boemund includes a cornucopia of elements which draw an analogy to other Byzantine literary portraits, it is highly likely that there existed a canon of description that was employed in historical works. It mostly applied to imperial portraits, however, the example of the Alexias proves that it could also have been utilised in the description of other exceptional characters. The Alexias also bears out the existence of a dichotomy between the schema of description of bad and good emperors. In Anna’s work it is clearly visible in the descriptive manner she adopted, on the one hand, in the portraits of Alexios, Robert and Boemund and, on the other hand, in the description of infant John, later emperor John I. Anna Komnena’s work is also another proof of popularity of physiognomical knowledge in Byzantium. It is worth noticing that she makes a reference to the most celebrated figure in the field of physiognomy, namely Polemo of Laodicea.